Act like you got some sense : and other things my daughters taught me - Foxx, Jamie; Chiles, Nick (Grand Central Publishing, 2021)
"In this hilarious and heartfelt memoir, award-winning, multi-talented entertainer Jamie Foxx shares the story of being raised by his no-nonsense grandmother, the glamour and pitfalls of life in Hollywood, and the lessons he took from both worlds to raise his two daughters"--